Relationship between Altmetrics and Citations A Study on the Highly Cited Research Papers - Heydari, Shabnam; Shekofteh, Maryam; Kazerani, Maryam (DESIDOC Journal of Library & Information Technology, 2019)
The present study aims to assess highly cited articles using altmetrics and citations and identify the relationship between them. The statistical population consists of all the highly cited articles on surgery indexed on the Web of Science. The number of article citations was measured using the Web of Science and the altmetric score of the articles using the Altmetric Bookmarklet. The analysis of the data was carried out using descriptive statistics and Spearman’s correlation coefficient. Of the 1077 highly cited surgery articles, 62.74 per cent had an altmetric score. The highest number of received citations was 1787, and the highest altmetric score was 2019. A positive and significant correlation was observed between the number of citations and the policy-making documents, Wikipedia citations and CiteULike (P<0.001). A positive but non-significant correlation was also observed between the number of citations and the number of Mendeley readers (r=0.02, P>0.05). A poor, negative and significant correlations were observed between the number of citations and the overall altmetric score of the highly cited surgery articles (r=-0.235, P<0.001). The findings may be due to the different pattern of using social media by the surgery researchers compared to the researchers of other fields. Altmetrics can only be used to complement citations and not replace them.